Transformation of English Language Teaching: Educator and Technology Integration at University - Hariadi Syam; La Sunra; Syarifuddin Dollah (Universitas Islam Negeri Palopo, 2026)
This study investigates how English Language Teaching (ELT) at Universitas Sembilanbelas November Kolaka is transforming through the integration of technology in lecturers’ instructional practices. The research addresses the need for digitalized and culturally relevant pedagogy in post-pandemic higher education and aims to analyze lecturers’ technological integration, challenges, and its impact on learning. Using a qualitative descriptive design, data were gathered through interviews, classroom observations, and document analysis involving seven lecturers and thirty students. The findings show that lecturers increasingly adopt digital tools to support interactive learning and develop stronger technological–pedagogical competence. Technology-enabled activities such as collaborative writing, multimedia tasks, and AI-assisted feedback enhanced classroom engagement. The study also reveals that incorporating local cultural content into digital lessons significantly improves student motivation, demonstrating the importance of culturally responsive approaches in technology-mediated ELT. These results highlight the need for institutional support to sustain meaningful digital transformation in higher education.